Method of Estimating the Equivalence of Dissolution Profiles: a Modern View (Review) - I. E. Shohin; N. S. Bagaeva; E. A. Malashenko; V. N. Kuzina (Разработка и регистрация лекарственных средств)
Introduction. One of the purposes of dissolution profile comparison is to establish the equivalence of dissolution profiles of the studied drug and the comparison drug.Text. According to the current regulatory documents, the main tool for quantitative confirmation of equivalence of drug release profiles is the calculation of the similarity factor (f2). However, it does not consider the form of dissolution profiles, incomplete release of the drug substance, time correlation, and is not susceptible to the «outliers», which leads to false positive results. Special attention should be paid to the dissolution of drugs with high variability, which is not eliminated by either increasing the sample or changing the sampling scheme. If f2 is not used, it is necessary to use model-dependent and model-independent methods that are statistically correct, and their use is sufficiently justified (difference factor f1, Weibull distribution function, comparison of release degrees at different time points (according to the student's t-criterion). However, these models have an empirical nature that calls into question the application of such methods. Multivariate analysis is widely discussed in the literature and can be used to compare the similarity of dissolution with the assumption that the data has a normal distribution. The most common methods for checking similarity of dissolution profiles for highly variable drugs are the Mahalanobis distance test and the bootstrap for f2. There is a document of EMA about suitability of the Mahalanobis distance as a tool to assess the comparability of drug dissolution profiles and to a larger extent to emphasise the importance of confidence intervals to quantify the uncertainty around the point estimate of the chosen metric. The bootstrap methodology for f2 does not provide a clear understanding of the application to dissolution profile comparison for incomplete-release drugs, particularly in biorelevant environments. The «T2EQ» function, based on the Mahalanobis distance for highly variable drugs (Hoffelder), gives undefined results in practice.Conclusion. The topic of equivalence of dissolution profiles requires discussion, since it is shown that the convergence factor is outdated and cannot be adequately applied. The use of modern methods does not have a clear regulatory confirmation by the regulatory authority. In the published scientific literature, several statistical methods have been explored and compared for their design and performance. It is necessary to develop a clear plan (decision treeы) for conducting the procedure for equivalence of dissolution profiles, employing a range of statistical methods.